Capsaicin restores sodium iodine symporter-mediated radioiodine uptake through bypassing canonical TSH‒TSHR pathway in anaplastic thyroid carcinoma cells. (9th November 2021) - Xu, Shichen; Cheng, Xian; Wu, Jing; Wang, Yunping; Wang, Xiaowen; Wu, Liying; Yu, Huixin; Bao, Jiandong; Zhang, Li
Abstract: Anaplastic thyroid cancer (ATC) is a rare but highly lethal disease. ATCs are resistant to standard therapies and are extremely difficult to manage. The stepwise cell dedifferentiation results in the impairment of the iodine-metabolizing machinery and the infeasibility of radioiodine treatment in ATC. Hence, reinducing iodine-metabolizing gene expression to restore radioiodine avidity is considered as a promising strategy to fight against ATC. In the present study, capsaicin (CAP), a natural potent transient receptor potential vanilloid type 1 (TRPV1) agonist, was discovered to reinduce ATC cell differentiation and to increase the expression of thyroid transcription factors (TTFs including TTF-1, TTF-2, and PAX8) and iodine-metabolizing proteins, including thyroid-stimulating hormone receptor (TSHR), thyroid peroxidase, and sodium iodine symporter (NIS), in two ATC cell lines, 8505C and FRO. Strikingly, CAP treatment promoted NIS glycosylation and its membrane trafficking, resulting in a significant enhancement of radioiodine uptake of ATC cells in vitro . Mechanistically, CAP-activated TRPV1 channel and subsequently triggered Ca 2+ influx, cyclic adenosine monophosphate (cAMP) generation, and cAMP-responsive element-binding protein (CREB) signal activation. Next, CREB recognized and bound to the promoter of SLC5A5 to facilitate its transcription. Moreover, the TRPV1 antagonist CPZ, the calcium chelator BAPTA, and the PKA inhibitor H-89 effectively alleviated the redifferentiation exerted by CAP, demonstrating that CAP might improve radioiodine avidity through the activation of the TRPV1‒Ca 2+ /cAMP/PKA/CREB signaling pathway. In addition, our study indicated that CAP might trigger a novel cascade to redifferentiate ATC cells and provide unprecedented opportunities for radioiodine therapy in ATC, bypassing canonical TSH‒TSHR pathway.